Method for collaborative recycling of copper in waste ferric trichloride etching liquid through metal sludge - ZHAO DONGKUI; LIN NENHAO; XU QUNCAI; YAN JUNJIANG (2017)
The invention relates to a method for collaborative recycling of copper in waste ferric trichloride etching liquid through metal sludge. That is, metal sludge pulping squeezing water and caustic soda flakes are prepared into alkaline pulping liquid in a pulping pool, the metal sludge of a fixed proportion is thrown and added into the alkaline pulping liquid, stirring is started, the metal sludge and the pulping liquid are mixed evenly, the waste ferric trichloride etching liquid is thrown and added into the pulping pool, the pH value of the pulping liquid is adjusted, and it is ensured that copper ions in the waste ferric trichloride etching liquid completely deposit. The mixed sludge in the pulping pool is pumped to a diaphragm press for squeezing and dewatering, part of the squeezing water can be reused for preparing alkaline pulping liquid, others can be directly subjected to biochemical treatment, the wastewater treatment cost is low, the generated squeezing sludge is briquetted and fed into a smelting fu